Resin composition
The resin composition with a nitrogen-free silane-treated white inorganic pigment enhances reflectance and flexibility, addressing the limitations of existing reflective plates for LED applications by providing high reflectance and heat resistance.
Patent Information
- Application Number
- JP2020152863
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-09-11
AI Technical Summary
Existing reflective plates for printed wiring boards used in LED applications have low reflectance and are not flexible enough to accommodate various light sources, particularly for mini-LEDs and micro-LEDs, and they degrade due to light oxidation.
A resin composition containing a white inorganic pigment surface-treated with a silane coupling agent lacking nitrogen atoms, combined with optional components like epoxy resin and silica, to enhance reflectance and flexibility while maintaining low melt viscosity.
The resin composition achieves a cured product with high reflectance before and after heat resistance tests, offering improved flexibility and reduced melt viscosity, suitable for reflective sheets and printed wiring boards.
Smart Images

Figure 0007600579000007 
Figure 0007600579000001 
Figure 0007600579000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition. The present invention further relates to a resin sheet, a reflecting sheet, and a printed wiring board obtained by using the resin composition. [Background technology]
[0002] Light-emitting diodes (LEDs), which emit light with low power, are increasingly being mounted directly on printed wiring boards for use as backlights for liquid crystal displays in mobile terminals, computers, televisions, etc., and as light sources for lighting fixtures.
[0003] A reflector for reflecting light is formed on the outermost layer of such a printed wiring board in order to increase the efficiency of extracting light emitted from the light source.
[0004] As a material for such a reflector, for example, a diffusing curable resin composition has been disclosed that contains a photosensitive carboxyl group-containing resin, a predetermined photopolymerization initiator, a photopolymerizable monomer, titanium oxide surface-treated with silica and alumina, an organic solvent, and at least one of barium sulfate and talc in a predetermined amount (see Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-212841 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the reflector made of the curable resin composition for diffusion described in Patent Document 1 has a low reflectance, and there is still room for improvement in using the reflector for mini LEDs and micro LEDs. In addition, the reflector is required to be flexible in order to accommodate various shapes of light sources.
[0007] The object of the present invention has been devised in view of the above-mentioned problems, and is to provide a resin composition having a low minimum melt viscosity, which can give a cured product having excellent reflectance before and after a heat resistance test; a resin sheet containing the resin composition; a reflective sheet; and a printed wiring board. [Means for solving the problem]
[0008] The present inventors conducted extensive research to solve the above problems and found that titanium oxide surface-treated with silica and alumina, as in the diffusion curable resin composition described in Patent Document 1, is oxidized by light, resulting in a decrease in reflectance. As a result of extensive research, the present inventors found that a cured product excellent in reflectance and reflectance after heat resistance testing can be obtained and further the minimum melt viscosity can be reduced by adding (A) a white inorganic pigment surface-treated with a silane coupling agent not containing a nitrogen atom to a resin composition, and thus completed the present invention.
[0009] That is, the present invention includes the following. [1] (A) A resin composition comprising a white inorganic pigment that has been surface-treated with a silane coupling agent that does not contain nitrogen atoms. [2] The resin composition according to [1], wherein the content of component (A) is 10% by mass or more and 60% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass. [3] The resin composition according to [1] or [2], further comprising (B) an epoxy resin. [4] The resin composition according to [3], wherein the content of component (B) is 1% by mass or more and 50% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass. [5] The resin composition according to any one of [1] to [4], wherein the component (A) is one or more selected from aluminum oxide, titanium oxide, zirconium oxide, magnesium oxide, barium titanate, zinc oxide, cerium oxide, and calcium carbonate. [6] The resin composition according to any one of [1] to [5], wherein the silane coupling agent not containing a nitrogen atom is one or more selected from a phenylsilane coupling agent, an alkylsilane coupling agent, an epoxysilane coupling agent, a vinylsilane coupling agent, a (meth)acrylicsilane coupling agent, and a styrylsilane coupling agent. [7] The resin composition according to any one of [1] to [6], further comprising (C) silica. [8] The resin composition according to any one of [1] to [7], which is for light reflection. [9] A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of [1] to [8].
[10] The resin sheet according to [9], wherein the resin composition layer has a minimum melt viscosity of 5,000 poise or less.
[11] A reflecting sheet comprising a cured product of the resin composition according to any one of [1] to [8].
[12] A printed wiring board comprising the reflective sheet according to
[11] .
[13] A printed wiring board comprising the cured reflective sheet according to
[11] as an interlayer insulating layer or a solder resist layer. Effect of the Invention
[0010] According to the present invention, it is possible to provide a resin composition having a low minimum melt viscosity and capable of giving a cured product having excellent reflectance before and after a heat resistance test; a resin sheet containing the resin composition; a reflective sheet; and a printed wiring board. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a printed wiring board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0013] [Resin composition] The resin composition of the present invention contains, as component (A), a white inorganic pigment that has been surface-treated with a silane coupling agent that does not contain a nitrogen atom. In the present invention, by including component (A), a cured product having excellent reflectance before and after a heat resistance test can be obtained, and a resin composition having a low minimum melt viscosity can be obtained.
[0014] The resin composition may further contain optional components in addition to the component (A). Examples of the optional components include an epoxy resin (B), silica (C), a curing agent (D), a curing accelerator (E), a thermoplastic resin (F), other additives (G), and an organic solvent (H). Each component contained in the resin composition will be described in detail below.
[0015] <(A) White inorganic pigment surface-treated with a silane coupling agent that does not contain nitrogen atoms> The resin composition contains, as component (A), a white inorganic pigment that has been surface-treated with a silane coupling agent that does not contain nitrogen atoms. By including component (A) in the resin composition, it is possible to obtain a cured product that has improved reflectance and reflectance after a heat resistance test.
[0016] In one embodiment, the white inorganic pigment refers to an inorganic compound having a reflectance of 90% or more for light having a wavelength of 500 nm, and the white inorganic pigment does not include (C) silica, which will be described later. The white inorganic pigment has a function of improving the reflectance. The white inorganic pigment may be used alone or in combination of two or more kinds.
[0017] Examples of white inorganic pigment materials include white metal oxides such as aluminum oxide (alumina), titanium oxide, zirconium oxide, magnesium oxide, zinc oxide, cerium oxide, antimony oxide, tin oxide, barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, barium titanate zirconate, barium zirconate, and calcium zirconate; white metal sulfides such as zinc sulfide and strontium sulfide; white metal hydroxides such as aluminum hydroxide, magnesium hydroxide, and calcium hydroxide; white metal nitrides such as boron nitride, aluminum nitride, and manganese nitride; calcium carbonate, barium carbonate, carbon dioxide, and the like. Examples of the white metal carbonates include magnesium carbonate, strontium carbonate, and lead carbonate; white metal sulfates include barium sulfate, calcium sulfate, and lead sulfate; white metal phosphates include zinc phosphate, titanium phosphate, zirconium phosphate, and zirconium tungstate phosphate; white metal borates include aluminum borate; and white minerals such as cordierite, talc, clay, mica, hydrotalcite, and boehmite. Among these, it is preferable to use one or more selected from aluminum oxide, titanium oxide, zirconium oxide, magnesium oxide, barium titanate, zinc oxide, cerium oxide, and calcium carbonate, and titanium oxide is particularly suitable. As the titanium oxide, any of rutile type, anatase type, and brookite type may be used, and among them, rutile type is preferable from the viewpoint of further improving the reflectance and the reflectance after the heat resistance test. Titanium oxide obtained by a method such as a sulfuric acid method or a chlorine method can be used. The material of the white inorganic pigment may be one type alone or a mixture of two or more types. The shape of the white inorganic pigment may be, for example, any of irregular, crushed, scaly, and spherical.
[0018] Examples of commercially available white inorganic pigments include "PX3788" manufactured by Sakai Chemical Industry Co., Ltd.; Typec "CR-50", "CR-57", "CR-80", "CR-90", "CR-93", "CR-95", "CR-97", "CR-60", "CR-63", "CR-67", "CR-58", "CR-85", and "UT771" manufactured by Ishihara Sangyo Kaisha; Typepure "R-100", "R-101", "R-102", "R-103", "R-104", "R-105", "R-108", "R-900", "R-902", "R-960", "R-706", and "R-931" manufactured by DuPont; "AHP300" manufactured by Nippon Light Metal Co., Ltd.; and Alnabeads "CB-P05" and "CB-A30S" manufactured by Showa Denko KK.
[0019] From the viewpoint of obtaining the effects of the present invention remarkably, the specific surface area of the white inorganic pigment is preferably 0.5 m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 2m 2 / g or more. There is no particular upper limit, but it is preferably 80m 2 / g or less, 70m 2 / g or less or 60m 2 The specific surface area is determined by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountec Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.
[0020] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the white inorganic pigment is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and is preferably 10 μm or less, more preferably 7 μm or less, even more preferably 5 μm or less.
[0021] The average particle size of the white inorganic pigment can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the white inorganic pigment is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of the white inorganic pigment and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample is measured using a laser diffraction particle size distribution measuring device with blue and red light source wavelengths used and a flow cell method to measure the particle size distribution of the white inorganic pigment on a volume basis, and the average particle size can be calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0022] The white inorganic pigment is surface-treated with a silane coupling agent that does not contain nitrogen atoms. By surface-treating the white inorganic pigment with a silane coupling agent that does not contain nitrogen atoms, it is possible to obtain a cured product that has excellent reflectance before and after a heat resistance test. In addition, by surface-treating the white inorganic pigment with a silane coupling agent that does not contain nitrogen atoms, the minimum melt viscosity of the resin composition is reduced, and flexibility can also be improved.
[0023] When a white inorganic pigment is surface-treated with a silane coupling agent containing nitrogen atoms, such as an aminosilane coupling agent, the nitrogen atoms contained in the silane coupling agent themselves are oxidized by light, causing the white inorganic pigment to turn yellow. In addition, the nitrogen atoms contained in the silane coupling agent act as a catalyst for photooxidation, promoting oxidation and deterioration of the cured product of the resin composition, resulting in a decrease in reflectance. In the present invention, the white inorganic pigment is surface-treated with a silane coupling agent that does not contain nitrogen atoms, so that the yellowing of the white inorganic pigment caused by the silane coupling agent is suppressed. In addition, the silane coupling agent that does not contain nitrogen atoms does not act as a catalyst itself, so that it is possible to suppress the decrease in reflectance of the cured product of the resin composition.
[0024] As the silane coupling agent that does not contain a nitrogen atom, a compound that does not contain a nitrogen atom and has two different functional groups in the molecule can be used. Examples of such silane coupling agents include phenylsilane coupling agents, alkylsilane coupling agents, epoxysilane coupling agents, vinylsilane coupling agents, (meth)acrylic silane coupling agents, and styrylsilane coupling agents. The silane coupling agent that does not contain a nitrogen atom may be used alone or in any combination of two or more types. Here, the (meth)acrylic silane coupling agent is a concept that includes both an acrylic silane coupling agent and a methacrylic silane coupling agent.
[0025] Examples of phenylsilane coupling agents include phenyltrimethoxysilane and phenyltriethoxysilane.
[0026] Examples of alkylsilane coupling agents include methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, and 1,6-bis(trimethoxysilyl)hexane.
[0027] Examples of epoxy silane coupling agents include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane.
[0028] Examples of vinylsilane coupling agents include vinyltrimethoxysilane and vinyltriethoxysilane.
[0029] Examples of the (meth)acrylsilane coupling agent include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane.
[0030] An example of the styrylsilane coupling agent is p-styryltrimethoxysilane.
[0031] Among these, the silane coupling agent not containing a nitrogen atom is preferably at least one selected from a phenylsilane coupling agent, an alkylsilane coupling agent, an epoxysilane coupling agent, a vinylsilane coupling agent, a (meth)acrylic silane coupling agent, and a styrylsilane coupling agent, more preferably at least one selected from a phenylsilane coupling agent, an epoxysilane silane coupling agent, and a (meth)acrylic silane coupling agent, and even more preferably a phenylsilane coupling agent.
[0032] Commercially available silane coupling agents not containing nitrogen atoms can be used. Commercially available silane coupling agents not containing nitrogen atoms include, for example, "KBM-103" and "KBE-103" (phenylsilane coupling agents) manufactured by Shin-Etsu Chemical Co., Ltd.; "KBM-13", "KBM-22", "KBE-13", "KBE-22", "KBM-3033", "KBE-3033", "KBM-3063", "KBE-3063", "KBE-3083", "KBM-3103C", "KBM-3066", and "KBM-7103" (alkylsilane coupling agents). coupling agents); "KBM-1003", "KBE-1003" (vinyl silane coupling agents); "KBM-303", "KBM-402", "KBM-403", "KBE-402", "KBE-403" (epoxy silane coupling agents); "KBM-1403" (styryl silane coupling agents); "KBM-502", "KBM-503", "KBE-502", "KBE-503", "KBM-5103" ((meth)acrylic silane coupling agents).
[0033] From the viewpoint of obtaining the effects of the present invention significantly, the degree of surface treatment with the silane coupling agent not containing a nitrogen atom is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.8 parts by mass or more, relative to 100 parts by mass of the white inorganic pigment, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 5 parts by mass or less.
[0034] Silane coupling agents that do not contain nitrogen atoms can be evaluated based on the amount of carbon per unit surface area of the white inorganic pigment. From the viewpoint of improving the dispersibility of the white inorganic pigment, the amount of carbon per unit surface area of the white inorganic pigment is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of suppressing an increase in the minimum melt viscosity of the resin composition and the minimum melt viscosity in the form of a sheet, it is more preferable that the content is 1 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable.2 The following is even more preferred:
[0035] The carbon amount per unit surface area of the white inorganic pigment can be measured after the surface-treated white inorganic pigment is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the white inorganic pigment that has been surface-treated with a silane coupling agent that does not contain nitrogen atoms, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the carbon amount per unit surface area of the white inorganic pigment can be measured using a carbon analyzer. The carbon analyzer that can be used is the "EMIA-320V" manufactured by Horiba, Ltd.
[0036] From the viewpoint of obtaining the effects of the present invention prominently, the content of the (A) component, relative to 100 mass% of the non-volatile components in the resin composition, is preferably 10 mass% or more, more preferably 15 mass% or more, even more preferably 20 mass% or more, and is preferably 60 mass% or less, more preferably 50 mass% or less, even more preferably 40 mass% or less, and particularly preferably 30 mass% or less. In the present invention, the content of each component in the resin composition is a value when the non-volatile components in the resin composition are taken as 100 mass %, unless otherwise specified.
[0037] Furthermore, from the viewpoint of achieving a remarkable effect of the present invention, the content of the silane coupling agent not containing a nitrogen atom in component (A) is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.15% by mass or more, and is preferably 1% by mass or less, more preferably 0.8% by mass or less, and even more preferably 0.5% by mass or less, when the non-volatile components in the resin composition are taken as 100% by mass.
[0038] From the viewpoint of obtaining the effects of the present invention prominently, the content of the white inorganic pigment excluding the silane coupling agent in the component (A) is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, and particularly preferably 30% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.
[0039] <(B) Epoxy resin> The resin composition may further contain an epoxy resin as component (B) as an optional component in addition to the above-mentioned components. The epoxy resin means a curable resin having an epoxy group. The epoxy resin (B) may be used alone or in combination of two or more kinds.
[0040] (B) Epoxy resins include, for example, bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, hydrogenated bisphenol A type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ether type epoxy resins, and the like. Examples of epoxy resins include ester type epoxy resins, cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, phenolphthalimidine type epoxy resins, and phenolphthalein type epoxy resins.
[0041] The resin composition preferably contains, as the (B) epoxy resin, an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the non-volatile components of the (B) epoxy resin is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0042] Epoxy resins include epoxy resins that are solid at a temperature of 25° C. (hereinafter sometimes referred to as "solid epoxy resins") and epoxy resins that are liquid at a temperature of 25° C. (hereinafter sometimes referred to as "liquid epoxy resins"). The resin composition of the present invention may contain only a solid epoxy resin as the epoxy resin (B), or may contain only a liquid epoxy resin, or may contain a combination of a solid epoxy resin and a liquid epoxy resin.
[0043] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.
[0044] As the solid epoxy resin, bixylenol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, naphthol novolac type epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, phenol aralkyl type epoxy resin, tetraphenylethane type epoxy resin, phenolphthalimidine type epoxy resin, and phenolphthalein type epoxy resin are preferred, and bisphenol AF type epoxy resin is more preferred.
[0045] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; and "EXA-73" manufactured by DIC Corporation. 11", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN475V" manufactured by Nippon Steel Chemical & Material Co., Ltd. (Naphthalene type epoxy resin); "ESN485" (Naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (Dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (Bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (Biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (Anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX77" manufactured by Mitsubishi Chemical Co., Ltd. Examples of epoxy resins include "PG-100" (phenol aralkyl type epoxy resin), "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals, "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical, "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical, "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical, "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical, and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. These may be used alone or in combination of two or more types.
[0046] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0047] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, hydrogenated bisphenol A type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, and epoxy resin having a butadiene structure are preferred, and bisphenol A type epoxy resin is more preferred.
[0048] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "825", and "Epicoat 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L" and "EP-3980S" (glycidylamine type epoxy resins) manufactured by ADEKA Corporation; Examples of epoxy resins include "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase Chemtex Corporation; "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) manufactured by Daicel Corporation; "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" (epoxy resin having a butadiene structure) manufactured by Nippon Soda Co., Ltd.; "ZX1658" and "ZX1658GS" (1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd., and "YX8000" (hydrogenated bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation. These may be used alone or in combination of two or more types.
[0049] The (B) epoxy resin may be any one of a solid epoxy resin, a liquid epoxy resin, or a combination thereof, but it preferably contains a solid epoxy resin, and it is particularly preferable that it is a combination of a solid epoxy resin and a liquid epoxy resin.
[0050] When a solid epoxy resin and a liquid epoxy resin are used in combination as the (B) epoxy resin, the mass ratio thereof (solid epoxy resin:liquid epoxy resin) is preferably 20:1 to 1:20, more preferably 10:1 to 1:10, and particularly preferably 3:1 to 1:3.
[0051] The epoxy equivalent of the (B) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 1,000 g / eq., even more preferably 80 g / eq. to 500 g / eq., and even more preferably 100 g / eq. to 300 g / eq. The epoxy equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0052] The weight average molecular weight (Mw) of the epoxy resin (B) is preferably from 100 to 5,000, more preferably from 250 to 3,000, and further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0053] From the viewpoint of prominently obtaining the effects of the present invention, the content of the (B) epoxy resin, relative to 100 mass% of the non-volatile components in the resin composition, is preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, particularly preferably 15 mass% or more, and is preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 35 mass% or less, and particularly preferably 30 mass% or less.
[0054] <(C) Silica> The resin composition of the present invention may further contain silica as component (C) as an optional component in addition to the above-mentioned components.
[0055] Examples of (C) silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, (C) silica is preferably spherical silica. The specific surface area and average particle size of (C) silica may be the same as those of (C) white inorganic pigment. (C) silica may be used alone or in combination of two or more kinds.
[0056] (C) Examples of commercially available silica products include "UFP-30" manufactured by Denka; "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; and "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs.
[0057] (C) Silica is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents such as 3,3,3-trifluoropropyltrimethoxysilane; aminosilane coupling agents such as 3-aminopropyltriethoxysilane, N-phenyl-8-aminooctyl-trimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane; epoxysilane coupling agents such as 3-glycidoxypropyltrimethoxysilane; mercaptosilane coupling agents such as 3-mercaptopropyltrimethoxysilane; silane coupling agents; alkoxysilanes such as phenyltrimethoxysilane; organosilazane compounds such as hexamethyldisilazane, and titanate coupling agents. Among them, the surface treatment agent is preferably an aminosilane coupling agent. Moreover, the surface treatment agent may be used alone or in any combination of two or more.
[0058] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).
[0059] The degree of surface treatment with the surface treatment agent is preferably within a predetermined range from the viewpoint of improving the dispersibility of (C) silica. Specifically, 100 parts by mass of (C) silica is preferably surface-treated with 0.2 parts by mass to 5 parts by mass of the surface treatment agent, more preferably 0.2 parts by mass to 3 parts by mass, and even more preferably 0.3 parts by mass to 2 parts by mass.
[0060] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of (C) silica. From the viewpoint of improving the dispersibility of (C) silica, the amount of carbon per unit surface area of (C) silica is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of suppressing an increase in the melt viscosity of the resin varnish and the melt viscosity in the form of a sheet, it is more preferable that the content is 1 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is more preferable: (C) The amount of carbon per unit surface area of silica can be measured in the same manner as for the white inorganic pigment.
[0061] From the viewpoint of obtaining the effects of the present invention prominently, the content of (C) silica, relative to 100 mass% of the non-volatile components in the resin composition, is preferably 5 mass% or more, more preferably 10 mass% or more, even more preferably 20 mass% or more, or 25 mass% or more, and is preferably 50 mass% or less, more preferably 45 mass% or less, and even more preferably 40 mass% or less.
[0062] From the viewpoint of significantly obtaining the effects of the present invention, the total content of the white inorganic pigment excluding the silane coupling agent in the component (A) and the component (C) is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, particularly preferably 50% by mass or more, and is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 75% by mass or less, and particularly preferably 70% by mass or less, based on 100% by mass of the non-volatile components in the resin composition.
[0063] When the content (mass%) of the (A) component is A1 and the content (mass%) of the (C) component is C1, assuming that the non-volatile components in the resin composition are 100 mass%, from the viewpoint of significantly obtaining the effects of the present invention, C1 / A1 is preferably 0.1 or more, more preferably 0.3 or more, and even more preferably 0.5 or more, and is preferably 10 or less, more preferably 5 or less, and even more preferably 3 or less.
[0064] <(D) Hardener> In addition to the above-mentioned components, the resin composition may further contain a curing agent as an optional component (D). The curing agent (D) has a function of reacting with the epoxy resin (B) to cure the resin composition. The curing agent (D) may be used alone or in combination of two or more kinds.
[0065] The (D) curing agent is not particularly limited, but examples thereof include phenol-based curing agents, carbodiimide-based curing agents, acid anhydride-based curing agents, amine-based curing agents, benzoxazine-based curing agents, cyanate ester-based curing agents, thiol-based curing agents, active ester-based curing agents, etc. The (D) curing agent preferably contains a phenol-based curing agent.
[0066] The phenol-based curing agent is a curing agent having two or more phenolic hydroxyl groups in one molecule, and examples thereof include bisphenol-based curing agents, biphenyl-type phenol-based curing agents, naphthalene-type phenol-based curing agents, phenol novolac-type phenol-based curing agents, naphthylene ether-type phenol-based curing agents, triazine skeleton-containing phenol-based curing agents, polyphenylene ether-type phenol-based curing agents, phenol aralkyl-type phenol-based curing agents, cresol novolac-type phenol-based curing agents, bisphenol-type phenol-based curing agents, and the like. Among these, preferred is a bisphenol-based curing agent, more preferred is a bisphenol-based curing agent selected from a bisphenol compound having a fluorine atom, a bisphenol compound having an alicyclic structure, and a bisphenol compound having a fluorene skeleton, still more preferred is a bisphenol compound having a fluorine atom, and particularly preferred is bisphenol AF.
[0067] Specific examples of commercially available phenol-based hardeners include "BiS-AF," "BiSOFP-A," "BiS-Z," and "BiSOC-FL," manufactured by Central Glass Co., Ltd.
[0068] The carbodiimide-based curing agent is a curing agent having two or more carbodiimide structures in one molecule, and examples of the curing agent include aliphatic biscarbodiimides such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide); Examples of polycarbodiimides include aromatic polycarbodiimides such as poly(methylenediphenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide].
[0069] Commercially available carbodiimide curing agents include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie.
[0070] The acid anhydride curing agent is a curing agent having one or more carboxylic acid anhydride groups (-CO-O-CO-) in one molecule, and examples thereof include phthalic anhydride, pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-diphenylethertetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, methylene-4,4' aromatic acid anhydride-based hardeners such as tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, cyclopentanetetracarboxylic dianhydride, cyclohexane-1,2,4,5-tetracarboxylic dianhydride, and the like; and polymeric anhydride-based hardeners such as styrene / maleic anhydride copolymer, and alkyl (meth)acrylate / styrene / maleic anhydride copolymer. Commercially available acid anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, and "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd.
[0071] The amine-based curing agent is a curing agent having two or more amino groups, and examples thereof include aliphatic amines, polyether amines, alicyclic amines, and aromatic amines. Among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of the amine-based curing agent include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, and the like. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. As the amine-based curing agent, commercially available products may be used, and examples thereof include "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.
[0072] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation; "HFB2006M" manufactured by Showa Polymer Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0073] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.
[0074] The thiol-based curing agent is a curing agent having two or more mercapto groups, and examples thereof include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0075] As the active ester curing agent, a compound having one or more active ester groups in one molecule can be used. Among them, as the active ester curing agent, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferred. The active ester curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred.
[0076] Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid.
[0077] Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0078] Preferred specific examples of the active ester curing agent include an active ester curing agent containing a dicyclopentadiene-type diphenol structure, an active ester curing agent containing a naphthalene structure, an active ester curing agent containing an acetylated product of phenol novolac, and an active ester curing agent containing a benzoylated product of phenol novolac. Among them, an active ester curing agent containing a naphthalene structure and an active ester curing agent containing a dicyclopentadiene-type diphenol structure are more preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structural unit consisting of phenylene-dicyclopentylene-phenylene.
[0079] Commercially available active ester curing agents include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" (manufactured by DIC Corporation) as active ester curing agents containing a dicyclopentadiene-type diphenol structure; "EXB9416-70BK" and "EXB-8150-65T" (manufactured by DIC Corporation) as active ester curing agents containing a naphthalene structure; and "EXB9416-70BK" and "EXB-8150-65T" (manufactured by DIC Corporation) as active ester curing agents containing an acetylated product of phenol novolac. Examples of such a hardener include "DC808" (manufactured by Mitsubishi Chemical Corporation); "YLH1026" (manufactured by Mitsubishi Chemical Corporation) as an active ester-based hardener containing a benzoyl derivative of phenol novolac; "DC808" (manufactured by Mitsubishi Chemical Corporation) as an active ester-based hardener which is an acetylated derivative of phenol novolac; and "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) as active ester-based hardeners which are benzoyl derivatives of phenol novolac.
[0080] The reactive group equivalent of the (D) curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the curing agent per equivalent of reactive group. For example, in the case of a phenol-based curing agent, the reactive group is a phenolic hydroxyl group. In the case of an acid anhydride-based curing agent, one equivalent of a carboxylic anhydride group (-CO-O-CO-) corresponds to two equivalents of reactive group.
[0081] From the viewpoint of significantly obtaining the effects of the present invention, the content of the (D) curing agent is preferably 1 mass % or more, more preferably 2 mass % or more, and even more preferably 3 mass % or more, and is preferably 50 mass % or less, more preferably 30 mass % or less, and even more preferably 10 mass % or less, based on 100 mass % of the non-volatile components in the resin composition.
[0082] <(E) Curing accelerator> The resin composition may contain a curing accelerator (E) as an optional component. The curing accelerator (E) has a function of accelerating the curing reaction of the epoxy resin (A). The curing accelerator (E) may be used alone or in combination of two or more kinds.
[0083] Examples of the (E) curing accelerator include phosphorus-based curing accelerators, imidazole-based curing accelerators, amine-based curing accelerators, guanidine-based curing accelerators, metal-based curing accelerators, etc. Among these, as the (E) curing accelerator, from the viewpoint of obtaining the effects of the present invention significantly, phosphorus-based curing accelerators and imidazole-based curing accelerators are preferred, and phosphorus-based curing accelerators are more preferred.
[0084] From the viewpoint of obtaining the effects of the present invention more prominently, the phosphorus-based curing accelerator preferably contains one or more selected from the group consisting of phosphonium salts and phosphines.
[0085] Examples of the phosphonium salt include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hydrogenhexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, and the like. Examples of aromatic phosphonium salts include aromatic phosphonium salts such as phenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate.
[0086] Examples of phosphines include aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine; dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, and tris(2,5-dimethylphenyl)phosphine. tris(2,6-dimethylphenyl)phosphine, tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2- Examples of aromatic phosphines include bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; and aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct.
[0087] As the phosphorus-based curing accelerator, commercially available products may be used, for example, "TBP-DA" manufactured by Hokko Chemical Industry Co., Ltd.
[0088] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2, 4-Diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-furan Examples of the imidazole compounds include imidazole compounds such as 2-ethyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.
[0089] As the imidazole-based curing accelerator, commercially available products may be used, for example, "P200-H50" manufactured by Mitsubishi Chemical Corporation, and "1B2PZ-10M" manufactured by Shikoku Kasei Co., Ltd.
[0090] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.
[0091] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.
[0092] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0093] From the viewpoint of prominently obtaining the effects of the present invention, the content of the (E) curing accelerator is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.3 mass% or more, based on 100 mass% of the non-volatile components in the resin composition, and is preferably 10 mass% or less, more preferably 7 mass% or less, and even more preferably 5 mass% or less.
[0094] <(F)Thermoplastic resin> The resin composition of the present invention may contain a thermoplastic resin (F) as an optional component. The thermoplastic resin (F) may be used alone or in combination of two or more kinds.
[0095] Examples of the (F) thermoplastic resin include phenoxy resin, polyvinyl acetal resin, acrylic resin, polyolefin resin, polybutadiene resin, polyimide resin, polyamideimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polyetherimide resin, polycarbonate resin, polyetheretherketone resin, and polyester resin. Of these, a resin selected from phenoxy resin, acrylic resin, and polyphenylene ether resin is preferred, and phenoxy resin is more preferred.
[0096] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. The phenoxy resin may be used alone or in combination of two or more. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton), "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.
[0097] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd., and S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0098] The acrylic resin refers to a polymer obtained by polymerizing a monomer component including a (meth)acrylic acid ester monomer. The monomer components constituting the acrylic resin may contain, in addition to the (meth)acrylic acid ester monomer, a (meth)acrylamide monomer, a styrene monomer, a functional group-containing monomer, or the like as copolymerization components. Specific examples of acrylic resins include "ARUFON UP-1000", "ARUFON UP-1010", "ARUFON UP-1020", "ARUFON UP-1021", "ARUFON UP-1061", "ARUFON UP-1080", "ARUFON UP-1110", "ARUFON UP-1170", "ARUFON UP-1190", "ARUFON UP-1500", "ARUFON UH-2000", "ARUFON UH-2041", "ARUFON UH-2190", "ARUFON UHE-2012", "ARUFON UC-3510", "ARUFON UG-4010", "ARUFON US-6100", and "ARUFON US-6170", all manufactured by Toagosei Co., Ltd. These may be used alone or in combination of two or more.
[0099] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin-based elastomers such as polypropylene and ethylene-propylene block copolymer.
[0100] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.
[0101] Specific examples of polyimide resins include "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd. Specific examples of polyimide resins also include modified polyimides such as linear polyimides obtained by reacting bifunctional hydroxyl-terminated polybutadiene, a diisocyanate compound, and a tetrabasic acid anhydride (polyimides described in JP-A-2006-37083), and polysiloxane skeleton-containing polyimides (polyimides described in JP-A-2002-12667 and JP-A-2000-319386, etc.).
[0102] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0103] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0104] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0105] Specific examples of polyphenylene ether resins include oligophenylene ether-styrene resins "OPE-2St1200" and "OPE-2St2200" manufactured by Mitsubishi Gas Chemical Co., Inc., and "NORYL SA90" manufactured by SABIC. Specific examples of polyetherimide resins include "Ultem" manufactured by GE.
[0106] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd. Specific examples of polyether ether ketone resins include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd. Examples of polyester resins include polyethylene terephthalate resins.
[0107] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the (E) thermoplastic resin is preferably 8,000 or more, more preferably 10,000 or more, and particularly preferably 20,000 or more, and is preferably 70,000 or less, more preferably 60,000 or less, and particularly preferably 50,000 or less.
[0108] The (F) thermoplastic resin is preferably a thermoplastic resin that, when formed into a film having a thickness of 20 μm, has a transmittance of 80% or more for light having a wavelength of 450 nm that is incident perpendicularly to the film surface.
[0109] From the viewpoint of significantly obtaining the desired effects of the present invention, the content of the (E) thermoplastic resin, relative to 100 mass% of the non-volatile components in the resin composition, is preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, and is preferably 30 mass% or less, more preferably 25 mass% or less, even more preferably 20 mass% or less.
[0110] <(G) Other Additives> The resin composition may further contain any additive as a non-volatile component. Examples of such additives include organic fillers such as rubber particles; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and salicylic acid-based ultraviolet absorbers; adhesion improvers such as urea silane; adhesion imparters such as triazole-based adhesion imparters, tetrazole-based adhesion imparters, and triazine-based adhesion imparters; hindered phenol-based antioxidants; fluorescent brighteners such as stilbene derivatives; fluorine-based Examples of the additives include surfactants such as surfactants and silicone surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester dispersants, polyoxyalkylene dispersants, acetylene dispersants, silicone dispersants, anionic dispersants, and cationic dispersants; and stabilizers such as borate stabilizers, titanate stabilizers, aluminate stabilizers, zirconate stabilizers, isocyanate stabilizers, carboxylic acid stabilizers, and carboxylic anhydride stabilizers. (G) Other additives may be used alone or in combination of two or more at any ratio. The content of (G) other additives can be appropriately determined by those skilled in the art.
[0111] <(H) Organic Solvent> The resin composition may further contain an arbitrary organic solvent as a volatile component in addition to the non-volatile components described above. As the (H) organic solvent, a known one can be appropriately used, and the type is not particularly limited. As the (H) organic solvent, for example, ketone-based solvents such as acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone, cyclohexanone, etc.; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, etc.; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, etc.; alcohol-based solvents such as methanol, ethanol, propanol, butanol, ethylene glycol, etc.; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methoxypropionic acid, etc. Examples of suitable organic solvents include ether ester solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (H) The organic solvent may be used alone or in combination of two or more in any ratio.
[0112] The content of the (H) organic solvent is not particularly limited, but when all components in the resin composition are taken as 100 mass%, it can be, for example, 80 mass% or less, 70 mass% or less, 60 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, 5 mass% or less, etc.
[0113] <Physical properties and applications of resin compositions> Since the resin composition of the present invention contains the component (A), a cured product having excellent reflectance and reflectance after a heat resistance test can be obtained. Furthermore, a resin composition having a low minimum melt viscosity can be obtained. Therefore, the resin composition of the present invention can be suitably used as a resin composition (light reflecting resin composition) for obtaining a cured product for light reflection applications for reflecting light from a light source. Specifically, it can be suitably used as a resin composition for a reflective sheet formed on the outermost layer of a printed wiring board. Examples of light sources include light emitting diodes (LEDs), mini LEDs, and micro LEDs. In addition, the resin composition of the present invention can be suitably used as a resin composition for insulating the solder resist layer of a printed wiring board. Therefore, the resin composition of the present invention can be suitably used as a resin composition for forming a layer that serves both as a solder resist layer and a reflective sheet. Furthermore, the resin composition of the present invention can be suitably used as a resin composition for interlayer insulation of a printed wiring board. Therefore, the resin composition of the present invention can be suitably used as a resin composition for forming an interlayer insulating layer.
[0114] The resin composition of the present invention contains the component (A), and therefore exhibits the characteristic of a low minimum melt viscosity. The minimum melt viscosity of the resin composition is preferably 5000 poise or less, more preferably 4500 poise or less, and even more preferably 4000 poise or less. The lower limit of the minimum melt viscosity is 100 poise or more, more preferably 500 poise or more, and even more preferably 1000 poise or more. Here, the term "minimum melt viscosity" refers to the minimum melt viscosity at 60°C to 200°C. The minimum melt viscosity can be measured using a dynamic viscoelasticity measuring device. The minimum melt viscosity can be measured according to the method described in the examples below. When the minimum melt viscosity of the resin composition is within this range, the resin composition has excellent flexibility.
[0115] The cured product obtained by curing the resin composition under the curing conditions of 180°C and 60 minutes exhibits the characteristic of excellent reflectance of light having a wavelength of 460 nm. Therefore, the cured product can reflect light with high reflectance, and for example, a reflective sheet with improved reflectance of light having a wavelength of 460 nm is obtained. The reflectance is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more. The upper limit of the reflectance may be 100% or less. The reflectance can be measured according to the method described in the examples below.
[0116] The resin composition is cured at 180°C for 60 minutes, and then subjected to a heat resistance test at 125°C for 100 hours. The cured product can reflect light with a high reflectance, and has excellent reflectance at a wavelength of 460 nm. Thus, the cured product provides a reflective sheet with improved reflectance at a wavelength of 460 nm after the heat resistance test. The reflectance after the heat resistance test is preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more. The upper limit of the reflectance after the heat resistance test can be 100% or less. The reflectance after the heat resistance test can be measured according to the method described in the examples below.
[0117] It is preferable that the cured product of the resin composition has a small decrease in reflectance due to the heat resistance test treatment. For example, the reflectance of the cured product obtained by curing the resin composition under the curing conditions of 180°C and 60 minutes is represented by ρ0 at a wavelength of 460 nm. The reflectance of the cured product after the heat resistance test treatment under the conditions of 125°C and 100 hours is represented by ρ1 at a wavelength of 460 nm. In this case, the decrease in reflectance due to the heat resistance test treatment, Δρ=ρ0-ρ1, is preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less.
[0118] [Resin sheet] The resin sheet of the present invention includes a support and a resin composition layer formed from the resin composition of the present invention provided on the support.
[0119] The thickness of the resin composition layer is preferably 200 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulation even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 5 μm or more, 10 μm or more, etc.
[0120] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0121] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0122] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0123] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.
[0124] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "PET501010", "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.
[0125] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.
[0126] In one embodiment, the resin sheet may further include other layers as necessary. Examples of such other layers include a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.
[0127] The resin sheet can be produced, for example, by preparing a resin varnish by directly applying a liquid resin composition or dissolving the resin composition in an organic solvent, applying this to a support using a die coater or the like, and then drying to form a resin composition layer.
[0128] The organic solvent may be the same as the organic solvent (H) above. The organic solvent may be used alone or in combination of two or more kinds.
[0129] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin composition (resin varnish), for example, when a resin composition (resin varnish) containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.
[0130] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0131] [Cured product] The cured product of the present invention is obtained by curing the resin composition of the present invention. The curing conditions of the resin composition may be the conditions of step (II) described below. In addition, the resin composition may be preheated before curing, and heating may be performed multiple times including preheating.
[0132] [Reflective sheets, printed wiring boards] The reflective sheet of the present invention includes a cured product of the resin composition of the present invention. The printed wiring board of the present invention includes the reflective sheet of the present invention. As shown in FIG. 1, the printed wiring board 1 has a reflective sheet 3 formed on a substrate 2, and a light source 4 is disposed on a surface 31 of the reflective sheet 3. Examples of the light source 4 include a light-emitting diode (LED), a mini LED, and a micro LED.
[0133] Since the reflective sheet contains the cured product of the resin composition of the present invention, it can reflect light with a high reflectance, and for example, the reflectance of light having a wavelength of 460 nm is preferably 90% or more, more preferably 94% or more, and even more preferably 95% or more. The upper limit of the reflectance can be 100% or less. Furthermore, since the reflective sheet contains the cured product of the resin composition of the present invention, it can reflect light with a high reflectance even after the heat resistance test treatment, and for example, the reflectance of light having a wavelength of 460 nm after the heat resistance test treatment is preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more. The upper limit of the reflectance after the heat resistance test treatment can be 100% or less. The reflectance and the reflectance after the heat resistance test treatment can be measured, for example, using a multichannel spectrometer (MCPD-7700, manufactured by Otsuka Electronics Co., Ltd.).
[0134] Since the reflective sheet contains the cured product of the resin composition of the present invention, it can also be contained as an interlayer insulating layer or a solder resist layer. Therefore, it is preferable that the printed wiring board of the present invention contains the reflective sheet as an interlayer insulating layer or a solder resist layer.
[0135] The printed wiring board and the reflecting sheet of the present invention can be produced, for example, by using the above-mentioned resin sheet by a method including the following steps (I), (II) and (III). (I) A step of laminating a resin sheet on a substrate so that the resin composition layer of the resin sheet is bonded to the substrate. (II) A step of thermally curing the resin composition layer to form a reflective sheet (III) A process of arranging a light source on the reflective sheet
[0136] The substrate used in step (I) is not limited, and may be, for example, a circuit board including an insulating layer, a conductor layer formed on the insulating layer, and a solder resist layer formed on the conductor layer. The insulating layer and the solder resist layer included in the circuit board may be formed using the reflective sheet of the present invention.
[0137] The substrate and the resin sheet can be laminated, for example, by thermocompression bonding the resin sheet to the substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the thermocompression bonding member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the substrate.
[0138] The substrate and the resin sheet may be laminated by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably carried out under reduced pressure conditions of 26.7hPa or less.
[0139] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.
[0140] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.
[0141] The support may be removed between step (I) and step (II) or after step (II).
[0142] In step (II), the resin composition layer is thermally cured to form a reflective sheet. For example, the thermal curing conditions for the resin composition layer vary depending on the type of resin composition, etc., but the curing temperature is preferably 120° C. to 240° C., more preferably 130° C. to 220° C., and even more preferably 150° C. to 210° C. The curing time can be preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.
[0143] Before curing the resin composition, the resin composition may be preheated at a temperature lower than the curing temperature. For example, prior to thermal curing of the resin composition, the resin composition may be preheated at a temperature of 50°C or higher and lower than 120°C (preferably 60°C or higher and 115°C or lower, more preferably 70°C or higher and 110°C or lower) for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes).
[0144] In order to increase the efficiency of extracting light emitted from the light source, the surface of the reflecting sheet facing the light source may have a recess in addition to being flat as shown in FIG.
[0145] In step (III), a light source is disposed on the reflective sheet. For example, when the reflective sheet has a recess on its surface, the light source is disposed in the recess.
[0146] If necessary, after electrically connecting the light source, the light source may be fixed by performing a sealing process or the like on the light source. EXAMPLES
[0147] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" mean "parts by mass" and "% by mass", respectively.
[0148] <White inorganic pigment used> White inorganic pigment 1: 100 parts of titanium oxide (average particle size 0.26 μm, Sakai Chemical Industry Co., Ltd. "PX3788") was surface-treated with 1 part of phenyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., molecular weight 198.1, "KBM-103") represented by the following structural formula (wherein Me represents a methyl group). [ka]
[0149] White inorganic pigment 2: 100 parts of titanium oxide (average particle size 0.26 μm, Sakai Chemical Industry Co., Ltd.'s "PX3788") was surface-treated with 3 parts of 3-glycidoxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.'s "KBM-403", molecular weight 236.1) represented by the following structural formula (wherein Me represents a methyl group). [ka]
[0150] White inorganic pigment 3: 100 parts of titanium oxide (average particle size 0.26 μm, Sakai Chemical Industry Co., Ltd. "PX3788") was surface-treated with 3 parts of 3-methacryloxypropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd., molecular weight 248.1, "KBM-503") represented by the following structural formula (wherein Me represents a methyl group). [ka]
[0151] White inorganic pigment 4: 100 parts of titanium oxide (average particle size 0.26 μm, Sakai Chemical Industry Co., Ltd.'s "PX3788") surface-treated with 3 parts of phenyltrimethoxysilane represented by the above structural formula (Shin-Etsu Chemical Co., Ltd.'s molecular weight 198.1, "KBM-103")
[0152] White inorganic pigment 5: 100 parts of titanium oxide (average particle size 0.26 μm, Sakai Chemical Industry Co., Ltd.'s "PX3788") was surface-treated with 0.6 parts of N-phenyl-3-aminopropyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.'s "KBM-573", molecular weight 255.1) represented by the following structural formula (wherein Me represents a methyl group). [ka]
[0153] White inorganic pigment 6: 100 parts of titanium oxide (average particle size 0.26 μm, "PX3788" manufactured by Sakai Chemical Industry Co., Ltd.) was surface-treated with 0.6 parts of 3-aminopropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., molecular weight 179.1) represented by the following structural formula (wherein Me represents a methyl group). [ka]
[0154] <Example 1> Four parts of a liquid bisphenol A type epoxy resin (epoxy equivalent 180, Mitsubishi Chemical Corporation's "Epikote 828EL"), four parts of a solid fluorine atom-containing epoxy resin (epoxy equivalent 245 g / eq., Mitsubishi Chemical Corporation's "YL7760"), and 20 parts of a phenoxy resin containing a biphenyl skeleton and a cyclohexane skeleton (Mitsubishi Chemical Corporation's "YX7200B35", weight average molecular weight 30,000, MEK solution with solids content of 35% by mass) were heated and dissolved in 8 parts of MEK with stirring. To this was added 10.1 parts of white inorganic pigment 1 (10 parts of titanium oxide, 0.1 part of silane coupling agent), 10 parts of spherical silica (average particle size 0.5 μm, Admattex Co., Ltd. "SO-C2", aminosilane treated), 4 parts of bisphenol AF (a solution of Central Glass Co., Ltd. "BiS-AF" adjusted with MEK to a non-volatile content of 50%), and 0.2 parts of phosphorus-based curing accelerator ((TBP-DA), Hokko Chemical Industry Co., Ltd.), and the mixture was uniformly dispersed using a high-speed rotating mixer to prepare resin composition 1.
[0155] A PET film with a release layer ("PET501010" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. Resin composition 1 was uniformly applied onto the release layer of this support so that the thickness of the resin composition layer after drying would be 50 μm. Thereafter, resin composition 1 was heated at 80° C. for 4 minutes to obtain resin sheet 1 including a resin composition layer with a thickness of 50 μm.
[0156] <Example 2> In Example 1, 10.1 parts of the white inorganic pigment 1 was changed to 10.3 parts of the white inorganic pigment 2 (10 parts of titanium oxide, 0.3 parts of silane coupling agent). A resin composition 2 and a resin sheet 2 were produced in the same manner as in Example 1 except for the above.
[0157] <Example 3> In Example 1, 10.1 parts of the white inorganic pigment 1 was changed to 10.3 parts of the white inorganic pigment 3 (10 parts of titanium oxide, 0.3 parts of silane coupling agent). A resin composition 3 and a resin sheet 3 were prepared in the same manner as in Example 1 except for the above.
[0158] <Example 4> In Example 1, 10.1 parts of the white inorganic pigment 1 was changed to 10.3 parts of the white inorganic pigment 4 (10 parts of titanium oxide, 0.3 parts of silane coupling agent). Resin composition 4 and resin sheet 4 were produced in the same manner as in Example 1 except for the above.
[0159] <Example 5> In Example 1, the amount of white inorganic pigment 1 was changed from 10.1 parts to 15.15 parts (15 parts of titanium oxide, 0.15 parts of silane coupling agent), and the amount of spherical silica (average particle size 0.5 μm, Admattex "SO-C2", aminosilane treated) was changed from 10 parts to 15 parts. Resin composition 5 and resin sheet 5 were produced in the same manner as in Example 1 except for the above.
[0160] <Example 6> In Example 1, the amount of white inorganic pigment 1 was changed from 10.1 parts to 20.2 parts, and spherical silica (average particle size 0.5 μm, Admatechs' "SO-C2", aminosilane-treated) was not used. Resin composition 6 and resin sheet 6 were produced in the same manner as in Example 1 except for the above.
[0161] <Example 7> In Example 1, 4 parts of the liquid bisphenol A type epoxy resin (epoxy equivalent 180, Mitsubishi Chemical Corporation's "Epicoat 828EL") was changed to 4 parts of a hydrogenated liquid epoxy resin (epoxy equivalent 205 g / eq., Mitsubishi Chemical Corporation's "YX8000"). Resin composition 7 and resin sheet 7 were produced in the same manner as in Example 1 except for the above points.
[0162] <Comparative Example 1> In Example 1, 10.1 parts of the white inorganic pigment 1 was changed to 10 parts of titanium oxide (average particle size 0.26 μm, "PX3788" manufactured by Sakai Chemical Industry Co., Ltd.) that had not been treated with a silane coupling agent. Resin composition 8 and resin sheet 8 were produced in the same manner as in Example 1 except for the above points.
[0163] <Comparative Example 2> In Example 1, 10.1 parts of the white inorganic pigment 1 was changed to 10.06 parts of the white inorganic pigment 5 (15 parts of titanium oxide, 0.06 parts of silane coupling agent). A resin composition 9 and a resin sheet 9 were prepared in the same manner as in Example 1 except for the above.
[0164] <Comparative Example 3> In Example 1, 10.1 parts of the white inorganic pigment 1 was changed to 10.06 parts of the white inorganic pigment 6 (15 parts of titanium oxide, 0.06 parts of silane coupling agent). A resin composition 10 and a resin sheet 10 were prepared in the same manner as in Example 1 except for the above points.
[0165] <Preparation of evaluation board A> (1) Surface preparation for inner layer circuit boards A circuit pattern was formed by etching on both sides of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Matsushita Electric Works "R5715ES") to produce an inner layer circuit board with an in-plane copper area of 30%. The copper circuit of the obtained inner layer circuit board was roughened with a micro-etching agent (Mec Co., Ltd. "CZ8100"). It was then dried at 190°C for 30 minutes.
[0166] (2) Lamination of resin sheet The resin sheets 1 to 10 prepared in each of the Examples and Comparative Examples were laminated on both sides of the inner layer circuit board prepared in (1) above using a batch type vacuum pressure laminator (MVLP-500, manufactured by Meiki Co., Ltd.). The resin sheets were laminated by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at 120°C for 30 seconds at a pressure of 0.74 MPa.
[0167] (3) Smoothing the resin sheet The laminated resin sheet was then heat-pressed at atmospheric pressure at 100° C. under a pressure of 0.5 MPa for 60 seconds to smooth the surface, and then the support was peeled off to obtain a substrate including a resin composition layer, an inner layer circuit board, and a resin composition layer in this order.
[0168] (4) Hardening of the resin sheet This substrate was cured at 180° C. for 60 minutes to obtain evaluation substrate A.
[0169] <Measurement of reflectance after curing> Evaluation substrate A was cut to a width of 50 mm and a length of 50 mm, and the cross section was polished. The reflectance of light with a wavelength of 460 nm was measured using a multichannel spectrometer (Otsuka Electronics Co., Ltd., MCPD-7700) and evaluated according to the following criteria. Evaluation criteria ◎: Reflectance is 95% or more ○: Reflectance is 90% or more but less than 95% △: Reflectance is 85% or more but less than 90% ×: Reflectance is less than 85%
[0170] <Measurement of reflectance after heat resistance test treatment> The above evaluation substrate A was heated at 125°C for 100 hours, cut into a piece 50 mm wide and 50 mm long, and the cross section was polished. The reflectance of light with a wavelength of 460 nm was measured using a multichannel spectrometer (Otsuka Electronics Co., Ltd., MCPD-7700) and evaluated according to the following criteria. Evaluation criteria ◎: Reflectance is 90% or more ○: Reflectance is 85% or more but less than 90% △: Reflectance is 80% or more but less than 85% ×: Reflectance is less than 80%
[0171] <Measurement of minimum melt viscosity> The dynamic viscoelasticity of the resin composition layers of the resin sheets 1 to 10 produced in the examples and comparative examples was measured using a dynamic viscoelasticity measuring device (Rheosol-G3000 manufactured by UBM Co., Ltd.) The measurements were performed from a starting temperature of 60°C to 200°C, with a heating rate of 5°C / min, an interval temperature of 2.5°C, and a vibration frequency of 1Hz / deg, and were evaluated according to the following criteria. 〇: Less than 5000poise. ×:Exceeds 5000 poise.
[0172] [Table 1] *The amount of component (A) and the total amount of component (C) refer to the total content of the white inorganic pigment which is a silane coupling agent not containing a nitrogen atom in component (A) and component (C) when the non-volatile components in the resin composition are taken as 100 mass %. [Explanation of symbols]
[0173] 1 Printed wiring board 2. Board 3 Reflective sheet 31 Reflective sheet surface 4 light source
Claims
1. A resin composition comprising: (A) a white inorganic pigment that has been surface-treated with a silane coupling agent that does not contain a nitrogen atom; (B) an epoxy resin; and (C) silica, The content of the component (A) is 10% by mass or more and 60% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass, (B) A resin composition, in which the epoxy resin comprises a combination of a solid epoxy resin and a liquid epoxy resin.
2. The resin composition according to claim 1 , wherein the content of the component (B) is 1% by mass or more and 50% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass.
3. 3. The resin composition according to claim 1, wherein the component (A) is at least one selected from the group consisting of aluminum oxide, titanium oxide, zirconium oxide, magnesium oxide, barium titanate, zinc oxide, cerium oxide, and calcium carbonate.
4. The resin composition according to any one of claims 1 to 3, wherein the silane coupling agent not containing a nitrogen atom is at least one selected from the group consisting of a phenylsilane coupling agent, an alkylsilane coupling agent, an epoxysilane coupling agent, a vinylsilane coupling agent, a (meth)acrylic silane coupling agent, and a styrylsilane coupling agent.
5. The resin composition according to any one of claims 1 to 4, which is for light reflection.
6. A resin sheet comprising a support and a resin composition layer provided on the support, the resin composition layer comprising the resin composition according to any one of claims 1 to 5.
7. The resin sheet according to claim 6 , wherein the resin composition layer has a minimum melt viscosity of 5,000 poise or less.
8. A reflecting sheet comprising a cured product of the resin composition according to any one of claims 1 to 5.
9. A printed wiring board comprising the reflective sheet according to claim 8.
10. A printed wiring board comprising the cured reflective sheet according to claim 8 as an interlayer insulating layer or a solder resist layer.
Citation Information
Patent Citations
Method for preparing flexible heat conducting insulating adhesive film used in LED heat radiation substrate
CN102676109A
Application of flexible thermal conductive insulation adhesive on LED (Light Emitting Diode) heat dissipation substrate
CN103409041A
Low-dielectric-loss high-heat-conductivity resin composition and preparation method thereof, and prepreg and laminated board prepared from resin composition
CN105585808A
Anisotropic conductive film and preparation method thereof
CN107286885A
Rubber with high abrasion resistance
CN107556565A
